Evaluation of the Topical Therapeutic Efficacy of Daidzein in Mitigating Inflammation and Rheumatoid Arthritis: Research Article (Journal of Pharma Insights and Research, 2025)
Rheumatoid arthritis (RA) is a debilitating autoimmune pathology characterized by chronic synovial inflammation and articular destruction. Current therapeutic modalities often entail significant adverse effects, necessitating the exploration of phytochemical alternatives with favorable safety profiles. Daidzein, a prominent soy-derived isoflavone, exhibits documented anti-inflammatory and antioxidant properties; however, its topical efficacy in arthritic models remains understudied. The present investigation elucidates the therapeutic potential of daidzein gel formulations (2% and 5% w/v) in mitigating acute and chronic inflammation using in vivo Wistar rat models. Antioxidant capacity was initially quantified via 2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide (H2O2) scavenging assays, revealing substantial free radical neutralization with IC50 values of 103.55 ± 1.62 µg/mL and 67.28 ± 0.14 µg/mL, respectively. Subsequently, anti-inflammatory efficacy was assessed through carrageenan-induced paw edema, while anti-arthritic potential was evaluated using the Complete Freund’s Adjuvant (CFA)-induced model over a 28-day period. Topical application of 5% daidzein gel showed a marked reduction in paw edema, exhibiting statistical parity with the standard non-steroidal anti-inflammatory drug, diclofenac. Specifically, the high-dose formulation significantly curtailed inflammatory progression in the chronic phase, normalizing paw volume measurements by day 28. These results substantiate the utility of daidzein as a potent bioactive agent capable of modulating oxidative stress and inflammatory cascades, thereby offering a viable adjunct strategy for the management of rheumatoid arthritis via topical administration